2018
DOI: 10.1038/s41385-018-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

C3a is required for ILC2 function in allergic airway inflammation

Abstract: Aberrant type 2 responses underlie the pathologies in allergic diseases like asthma, yet, our understanding of the mechanisms that drive them remains limited. Recent evidence suggests that dysregulated innate immune factors can perpetuate asthma pathogenesis. In susceptible individuals, allergen exposure triggers the activation of complement, a major arm of innate immunity, leading to the aberrant generation of the C3a anaphylatoxin. C3 and C3a have been shown to be important for the development of Th2 respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 55 publications
4
31
0
Order By: Relevance
“…For this purpose, we utilized established murine models of allergic eye disease (AED) and ocular graft-versus-host disease (GVHD) (Herretes et al, 2015; Lee et al, 2015). Our rationale for this is that complement has been implicated in the etiology of systemic GVHD and allergic inflammation (Gour et al, 2018; Kwan et al, 2012; Ma et al, 2014; Nguyen et al, 2018; Zhang and Köhl, 2010). However, a neuroinflammatory role of complement has not been described for either disease within the eye.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we utilized established murine models of allergic eye disease (AED) and ocular graft-versus-host disease (GVHD) (Herretes et al, 2015; Lee et al, 2015). Our rationale for this is that complement has been implicated in the etiology of systemic GVHD and allergic inflammation (Gour et al, 2018; Kwan et al, 2012; Ma et al, 2014; Nguyen et al, 2018; Zhang and Köhl, 2010). However, a neuroinflammatory role of complement has not been described for either disease within the eye.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that although the fraction of fucosylated lung epithelial cells is significantly increased upon IL-33 or papain stimulation, the UEA-I staining may underestimate its extent, because Tátrai et al reported that some parts of lung cells were inaccessible to UEA-I. 9 We also found that Fut2 deficiency is associated with reduced production of C3a, which has the capacity to enhance the recruitment and activation of ILC2s, 7…”
Section: Mice Lacking Fucosyltransferase 2 Show Reduced Innate Allergmentioning
confidence: 51%
“…Activated complements are associated with the pathogenesis of inflammation. C3a and C5a can induce anaphylactic mediators, such as histamine release and attract phagocytes to the sites 29,30 ; C5b‐9 induces target cell apoptosis 31 . These factors from complement activation are closely associated with the pathogenesis of inflammation 32 …”
Section: Discussionmentioning
confidence: 99%